Pengembangan Alat Ukur Regulasi Emosi pada Dewasa Awal Berdasarkan Model Proses Gross - Eklyn Naiyazalwa Nandhitya; Hanifaa Nida ‘An Khafiyya; Kania Aulia Nursyifa; Rahma Arinda Putri Bhirawanto; Dimas Fauzy Bahtiar; Novita Sari; Shananda Yulistia Azzahra (Jurnal Ragam Pengabdian, 2026)
This study aimed to develop and validate an emotion regulation measurement instrument for emerging adults based on Gross's (1998) process model of emotion regulation, which encompasses five strategies: situation selection, situation modification, attentional deployment, cognitive change, and response modulation. The need for this instrument arises from the limitations of existing tools such as the ERQ and DERS, which were developed within Western cultural contexts and therefore fail to adequately capture the emotional dynamics of Indonesian individuals, whose emotion regulation is strongly shaped by social norms and local cultural values. A total of 218 emerging adults aged 18–40 years participated in this study. The instrument was developed through content validity assessment using Aiken's V index, reliability estimation using Cronbach's Alpha and McDonald's omega coefficients, and construct validity testing via Confirmatory Factor Analysis (CFA). Results showed that all 24 items obtained Aiken's V values above 0.80, confirming strong content validity. Cronbach's Alpha of 0.878 and omega of 0.882 demonstrated high internal consistency. The final CFA model after modification yielded acceptable fit indices: χ²/df = 1.340, CFI = 0.955, RMSEA = 0.040, and SRMR = 0.064. Overall, this instrument is proven valid and reliable, and is more comprehensive than Western-based tools as it measures emotion regulation across the full spectrum from anticipatory strategies to response modulation, making it a culturally relevant assessment tool and a scientific basis for designing psychological interventions for emerging adults in Indonesia.